Correction: Music listening evokes story-like visual imagery with both idiosyncratic and shared content. - Sarah Hashim; Lauren Stewart; Mats B Küssner; Diana Omigie (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0293412.].